Lectio sanctarum scripturarum y exégesis en las obras de Isidoro de Sevilla - María Adelaida Andrés Sanz (Mélanges de la Casa de Velázquez, 2019)
This article studies the lectio divina as it appears in the works of Isidore of Seville from the point of view of its conception and practice. On the one hand, the article presents the Isidore's recommandations concerning the task of the Christian man (mainly in his Sententiae 3, 8 and Regula monachorum 5, 98-99). On the other hand, it points out the main characteristics of the exegetical work of the Sevillian bishop (collected in the Quaestiones in Vetus Testamentum, the Liber numerorum, and the series Prooemia, De ortu et obitu patrum and Allegoriae Sacrae Scripturae, as well as in several exegetical lines of these and other works of his copied in biblical codices). Finally, the article notes that a broad and profound study of exegesis in Isidore of Seville is still a pending investigation.